Intake of low sodium salt substitute for 3years attenuates the increase in blood pressure in a rural population of North China — A randomized controlled trial - Zhou, Bo; Webster, Jacqui; Fu, Ling-Yu; Wang, Hai-Long; Wu, Xiao-Mei; Wang, Wen-Li; Shi, Jing-Pu (International journal of cardiology, 2016)
Lowering salt intake is one of the successful and cost-effective methods to reduce blood pressure (BP). In this randomized controlled study, we investigated the effects of a 3-year substitution of table salt with a low-sodium salt substitute in a rural population of North China. Subjects from 200 families residing in five villages in Liaoning, North China were registered in this study and randomly divided into two groups: normal salt (100% sodium chloride) and low salt substitute (65% NaCl, 25% KCl, 10% MgSO4). We compared the effects of the low-sodium salt substitute and normal salt on differences in BP from baseline to various follow-up time points during this 3-year study period. We also examined several factors that may affect the long-term changes in BP. Hypertension was defined per World Health Organization guidelines as BP≥140/90mmHg. The low sodium substitute significantly reduced the increase in both systolic and diastolic BP compared with the regular salt (P=0.000). Also, the population aged 40–70years showed most beneficial response to the salt substitute compared with those aged <40 or >70years. The low salt substitute had similar beneficial effects in both males and females. In addition, the salt type consumed and body mass index significantly affected the change in BP. Use of the salt substitute significantly reduces the increase in BP over a long term, and thus, the salt substitute can be used as a replacement for regular salt in the daily diet to prevent/diminish the incidence of hypertension.